Utility of immune checkpoint inhibitors in non‐small‐cell lung cancer patients with poor performance status - Kano, Hirohisa (Cancer Sci, 2020)
Most clinical trials of non‐small‐cell lung cancer (NSCLC) exclude patients with poor ECOG performance status (PS). Thus, the efficacy of immune checkpoint inhibitors (ICIs) in patients with poor PS remains unclear. Herein, we used data from a retrospective cohort to assess the potential clinical benefits of ICIs in NSCLC patients with poor PS. Data from NSCLC patients who received ICI monotherapy at 9 institutions between December 2015 and May 2018 were retrospectively analyzed. After excluding 4 patients who lacked PS data, a total of 527 ICI‐treated patients, including 79 patients with PS 2 or higher, were used for our analyses. The progression‐free survival (PFS) and overall survival (OS) of patients with PS 2 or higher were significantly shorter compared with those of PS 0‐1 patients (median PFS, 4.1 vs 2.0 months; P < .001 and median OS, 17.4 vs 4.0 months; P < .001). Among NSCLC patients with programmed cell death protein‐ligand 1 (PD‐L1) expression of 50% or higher who were treated with pembrolizumab as first‐line therapy, the median PFS times of patients with PS 2 and 0‐1 were 7.3 and 8.1 months, respectively. There was no significant difference in PFS between patients with PS 2 and 0‐1 (P = .321). Although poor PS was significantly associated with worse outcomes in NSCLC patients treated with ICIs, pembrolizumab as a first‐line treatment in NSCLC patients expressing high levels of PD‐L1 could provide a clinical benefit, even in patients with PS 2.